Kidney Cancer in Canada: The Rapidly Increasing Incidence of Adenocarcinoma in Adults and Seniors - Liu, Shiliang (Can J Public Health, 1997)
Purpose: To examine kidney cancer incidence and mortality patterns since 1969 in Canada. Method: Linear regression of the log rates was used to estimate secular trends by age group and sex, and age-period-cohort models were fitted to examine changes in kidney cancer and renal adenocarcinoma incidence rates. Results: A substantial increase in incidence rates was observed among those 35 years and older, with average increases of 2.5% or more annually for both sexes. Age-period-cohort modelling suggested that much of this increase resulted from a period effect. Changes in mortality were much more modest, especially among those aged 0–34, for whom mortality rates actually declined by an average of 4.2% and 5.4% annually for males and females respectively. Conclusions: Kidney cancer incidence rates have increased significantly, especially renal adenocarcinoma among adults and seniors. Diagnostic improvements and increasing levels of obesity in the Canadian population may have contributed to these trends.